Power of Knowledge: Effect of Two Educational Interventions on Readiness for Chlamydia Screening. (July 2016) - Sagor, Rachel S.; Golding, Jeremy; Giorgio, Margaret M.; Blake, Diane R.
We compared ( a ) the effectiveness of print versus digital educational media for communicating information about Chlamydia trachomatis to adolescents and young adults and ( b ) the influence of media type on readiness for Chlamydia screening. Young men and women (n = 103), aged 15 to 24 years, were recruited from a youth center and university campus and randomized to receive the print or digital Chlamydia educational intervention. Participant mean knowledge score improved postintervention, but there was no association with type of intervention medium. Nearly two-thirds (61%) of sexually active participants endorsed an increased postintervention stage of readiness for screening; however, there was no association with type of intervention medium. Learning about Chlamydia infection may have positive effects on willingness to be screened. Further study is needed to evaluate the efficacy of educational interventions for increasing actual screening rates.